NIGERIAN NURSES AND MIDWIVES UNEMPLOYMENT SURVEY - RN, EGWUENU; RN, G.I. NSHI (International Journal of Research -GRANTHAALAYAH, 2020)
Background: The quacking controversy that trailed the Nursing & Midwifery Council of Nigeria’s (N&MCN) release of a “License Community Nurse (LCN)” circular (Ref No. N&MCN/SG/RO/CIR/24/VOL.4/152 dated March 3, 2020) which conveyed the intention of the council to lower the existing standard of nursing education for the LCN programme that will take secondary school leavers at least a credit in English and Biology to be admitted into and two years to complete, and inter alia blamed the crude situation and abysmal performance of the Nigerian Primary Healthcare (PHC) system in the community settings on mass migration of Nurses & Midwives to urban areas and to other countries prompted UGONSA to initiate this survey to empirically determine whether there are indeed a shortage of Nurses & Midwives to fill the manpower need of the Nigerian PHC system in the community settings or not, or whether the shortage is as a result of the deliberate age-long policy of attrition and displacement of Nurses & Midwives from the PHC system in the community settings and their replacement with Community Health Extension Workers (CHEWs) [who do not have nursing education, training, skills or the ethical leaning to be responsible and accountable for nursing & midwifery services] by the National Primary Healthcare Development Agency (NPHCDA). Objective: The main aim of the study was to determine if there is a shortage of nurses that could fill the nursing needs of the PHC system in the community settings. The study also sought to compile the list of unemployed and underemployed Nurses & Midwives and to find out if unemployed Nurses & Midwives are willing to work in the community settings if the opportunity to serve the PHC system in the community setting is offered to them by the NPHCDA. The study further sought to determine the ratio of unemployed Nurses & Midwives in relation to the possible number of graduates that can be licensed by the N&MCN in a session. Methods: Using Google forms an online compilation was carried out from March 7 to April 08, 2020, in a descriptive survey of unemployed Nurses & Midwives that could be reached online within the timeline. Names, Phone numbers, State of Residence, Year of Graduation, Qualification(s), and how long they have remained unemployed after graduation were compiled. In addition, two questions were asked about the objective of the study. Analysis of data was done via Google forms statistical tools. Results: A total of 3317 unemployed Nurses & Midwives responded to the survey. Among these unemployed Nurses & Midwives – 38% holds RN only, 19% holds both RN & RM, 15.4% holds RM only, while 27.6% holds BNSc plus another qualification. For the year they have remained unemployed after graduation 57.1% have spent 0–2 years, 29.9% have been unemployed for 3–5 years, 7% have been unemployed for 6 – 8 years and 6.1% have been unemployed for more than 8 years. To the question, “Do you think there is a shortage of Nurses and Midwives in Nigeria?” – 47.5% said yes, 43.5% said no whereas 9% were undecided (said maybe). Furthermore, the result showed that while 95% of the unemployed Nurses & Midwives are willing to work in the rural community settings, 1% was not willing to work in the rural community settings and 4% were undecided (.i.e. said maybe) on whether they will work in the rural community settings or not. The result also revealed that the 3317 unemployed Nurses & Midwives captured in the survey represents graduates of 66 Nursing & Midwifery schools per session out of a total of 162 schools that are currently accredited by the N&MCN. This represents 41% of the possible number of graduates that can be turned out of the accredited Nursing & Midwifery Schools (excluding Post-basic schools) in a session. Conclusion: Despite the reported migration of Nurses to urban areas and other countries, at least 41% of Nigerian Nurses & Midwives produced in a session remain unemployed and 95% of them are willing to work in the rural community settings if given the opportunity. These unemployed Nurses & Midwives can bridge the Nursing & Midwifery manpower needs in the Primary Healthcare System should the NPHCDA engage their services with a commensurate or higher payment to what their employed counterparts receive in Federal Government-owned establishments and hospitals. There is no current shortage of Nurses that necessitates the lowering of the existing standard of nursing education. Nurses & Midwives are not responsible for the design, implementation, and delivery of healthcare services at the PHC level and therefore are not culpable for the deplorable condition and abysmal performance of the Nigerian PHC System.